Zinc finger nuclease‐mediated precision genome editing of an endogenous gene in hexaploid bread wheat (Triticum aestivum) using a DNA repair template. Issue 12 (28th May 2018) - Ran, Yidong; Patron, Nicola; Kay, Pippa; Wong, Debbie; Buchanan, Margaret; Cao, Ying‐Ying; Sawbridge, Tim; Davies, John P.; Mason, John; Webb, Steven R.; Spangenberg, German; Ainley, William M.; et al.
Summary: Sequence‐specific nucleases have been used to engineer targeted genome modifications in various plants. While targeted gene knockouts resulting in loss of function have been reported with relatively high rates of success, targeted gene editing using an exogenously supplied DNA repair template and site‐specific transgene integration has been more challenging. Here, we report the first application of zinc finger nuclease (ZFN)‐mediated, nonhomologous end‐joining (NHEJ)‐directed editing of a native gene in allohexaploid bread wheat to introduce, via a supplied DNA repair template, a specific single amino acid change into the coding sequence of acetohydroxyacid synthase ( AHAS ) to confer resistance to imidazolinone herbicides. We recovered edited wheat plants having the targeted amino acid modification in one or more AHAS homoalleles via direct selection for resistance to imazamox, an AHAS‐inhibiting imidazolinone herbicide. Using a cotransformation strategy based on chemical selection for an exogenous marker, we achieved a 1.2% recovery rate of edited plants having the desired amino acid change and a 2.9% recovery of plants with targeted mutations at the AHAS locus resulting in a loss‐of‐function gene knockout. The latter results demonstrate a broadly applicable approach to introduce targeted modifications into native genes for nonselectable traits. All ZFN‐mediated changes were faithfully transmitted to the next generation.